Growth of the C(4) dicot Flaveria bidentis: photosynthetic acclimation to low light through shifts in leaf anatomy and biochemistry - Pengelly, Jasper J. L. (Oxford University Press, 2010)
In C(4) plants, acclimation to growth at low irradiance by means of anatomical and biochemical changes to leaf tissue is considered to be limited by the need for a close interaction and coordination between bundle sheath and mesophyll cells. Here differences in relative growth rate (RGR), gas exchange, carbon isotope discrimination, photosynthetic enzyme activity, and leaf anatomy in the C(4) dicot Flaveria bidentis grown at a low (LI; 150 μmol quanta m(2) s(−1)) and medium (MI; 500 μmol quanta m(2) s(−1)) irradiance and with a 12 h photoperiod over 36 d were examined. RGRs measured using a 3D non-destructive imaging technique were consistently higher in MI plants. Rates of CO(2) assimilation per leaf area measured at 1500 μmmol quanta m(2) s(−1) were higher for MI than LI plants but did not differ on a mass basis. LI plants had lower Rubisco and phosphoenolpyruvate carboxylase activities and chlorophyll content on a leaf area basis. Bundle sheath leakiness of CO(2) (ϕ) calculated from real-time carbon isotope discrimination was similar for MI and LI plants at high irradiance. ϕ increased at lower irradiances, but more so in MI plants, reflecting acclimation to low growth irradiance. Leaf thickness and vein density were greater in MI plants, and mesophyll surface area exposed to intercellular airspace (S(m)) and bundle sheath surface area per unit leaf area (S(b)) measured from leaf cross-sections were also both significantly greater in MI compared with LI leaves. Both mesophyll and bundle sheath conductance to CO(2) diffusion were greater in MI compared with LI plants. Despite being a C(4) species, F. bidentis is very plastic with respect to growth irradiance.